A 10-Year Cardiovascular Risk in Adults with Different Levels of Spiritual Health: Tehran Lipid and Glucose Study - Parisa Amiri; Fataneh Ghadirian; Parnian Parvin; Leila Cheraghi; Davood Khalili; Shahram Alamdari; Fereidoun Azizi (Ubiquity Press, 2023)
Background: Previous studies have shown that spiritual experience may reduce cardiovascular disease (CVDs). However, little is known about the relationship between spiritual health and the gender-specific risk of CVDs in communities with different cultures. Methods: A total of 3249 individuals (53.7% female, 75.0% middle-aged) participated in the Tehran Lipid and Glucose Study (TLGS) from 2015 to 2017 were included. Based on the ACC/AHA pooled cohort equation, CVD risk over ten years was examined. Spiritual health was measured using a developed tool for measuring spiritual health in Muslim populations (SHIMA-48). Linear regression models were used to assess the association between spiritual health and ACC/AHA risk scores. The natural logarithm scale was calculated to consider the normal distribution hypothesis of the regression model. Results: The current results suggest a slight but significant increase in the mean of spiritual health in women compared to men in both cognitive/emotional and behavioral dimensions (P < 0.001). In both sexes, a higher prevalence of smoking was observed in participants with lower levels of spiritual health (P < 0.004). In men, compared to those with a low level of spiritual health (the first tertile), the logarithm of the ACC-AHA risk score was reduced by 0.11 (P = 0.004) and 0.18 (P < 0.001) for those in the second and third tertiles of spiritual health, respectively. This result may be attributed to higher cigarette smoking among the latter group. Similar results were not observed in women. Conclusions: Current results indicate a gender-specific association between spiritual health and cardiovascular disease risk. Our findings imply that promoting spiritual health can be considered an effective strategy in future preventive interventions, primarily by controlling the desire to smoke in men.